2016
DOI: 10.1093/nar/gkw212
|View full text |Cite
|
Sign up to set email alerts
|

RNA Polymerase I and Fob1 contributions to transcriptional silencing at the yeast rDNA locus

Abstract: RNA polymerase II (Pol II)-transcribed genes embedded within the yeast rDNA locus are repressed through a Sir2-dependent process called ‘rDNA silencing’. Sir2 is recruited to the rDNA promoter through interactions with RNA polymerase I (Pol I), and to a pair of DNA replication fork block sites (Ter1 and Ter2) through interaction with Fob1. We utilized a reporter gene (mURA3) integrated adjacent to the leftmost rDNA gene to investigate localized Pol I and Fob1 functions in silencing. Silencing was attenuated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Both Fob1 and Smc5/6 physically and genetically interact with Sir214, [35][36][37][48][49][50][51] recovery at NTS1 in smc6-9 was similar to wild type, however consistent with previous reports14 its association at NTS1 was Fob1-dependent as Sir2 was equally reduced in fob1Δ and smc6-9 fob1Δ mutants (Fig. 4c).…”
Section: Smc5/6 Complex Plays a Fob1-independent Role In Modulating Lsupporting
confidence: 91%
See 1 more Smart Citation
“…Both Fob1 and Smc5/6 physically and genetically interact with Sir214, [35][36][37][48][49][50][51] recovery at NTS1 in smc6-9 was similar to wild type, however consistent with previous reports14 its association at NTS1 was Fob1-dependent as Sir2 was equally reduced in fob1Δ and smc6-9 fob1Δ mutants (Fig. 4c).…”
Section: Smc5/6 Complex Plays a Fob1-independent Role In Modulating Lsupporting
confidence: 91%
“…A shorter lifespan has been attributed to rDNA instability arising from increased collisions between replication and transcription machineries when chromatin was not silenced at NTS152. Fob1 binding at the RFB is central in this process and Smc5/6 is also linked, as it modulates HR processing at stalled replication forks14, 16,19,37,38,49,53,54 and here we show transcriptional silencing at NTS1. Previous work has shown that the reduced lifespan of sir2Δ mutants is suppressed by deleting FOB151.…”
Section: Smc5/6 Complex Plays a Fob1-independent Role In Modulating Lmentioning
confidence: 51%
“…Indeed, topoisomerase I is required for rDNA silencing, and a lack of TOP1 results in accumulation of negative supercoiling in the rDNA genes, presumably due to the selective relaxation of positive supercoils by another topoisomerase French et al 2011). Also consistent with a supercoiling model, transcriptional elongation by Pol I was shown to be necessary for downstream silencing (Buck et al 2016).…”
Section: Intracellular Competition For Limiting Amounts Of Sir2mentioning
confidence: 66%
“…Fob1 typically binds two cis-acting sequences within the RFB, known as Ter1 and Ter2 (Kobayashi 2003;Mohanty and Bastia 2004). Only Ter2 remains at the left flank, resulting in attenuated recruitment of RENT and suboptimal silencing (Bairwa et al 2010;Buck et al 2016). Nevertheless, binding of RENT nucleates a Sir2-dependent structure that spreads into the adjoining chromatin in a fashion analogous to spreading by the Sir2/3/4 complex at HM loci and telomeres (Buck et al 2002).…”
Section: Intracellular Competition For Limiting Amounts Of Sir2mentioning
confidence: 99%
“…Silencing appears to be the direct consequence of histone deacetylation by Sir2. The Sir2 enzyme-containing protein complex is recruited to Fob1 (in a Top1-dependent manner ( 17 , 84 )) and also to the Pol I promoter ( 96 ).…”
Section: Discussionmentioning
confidence: 99%